ANALISIS IMPLEMENTASI KEBIJAKAN KAWASAN TANPA ROKOK DI UNIVERSITAS X JAKARTA BARAT TAHUN 2019 - Wiraatmadja, Jesica; Ayu, Ira Marti (Health Publica, 2020)
AbstractX University published the Rector's Decision Letter which decided to be a non-smoking area, but within X University there are still smokers. This research objective was to determine the analysis of non-smoking area policy implementation at the X University, West Jakarta in 2019. This research used a qualitative method by conducting in-depth interviews, observations, and document reviews. The informants of this research were 9 people. The results of the research from the communication variable that there was already a media used to deliver the message, a clear reprimand was done even though it wasnâ€™t done consistently. From the resource variable, the human resources that involved is the all of the University citizens, but in the process of implementation, those directly involved are the General Bureau and Student Affairs Bureau as the person in charge, Vice-Rector 3, the Student President (BEMU chairperson), and Security as the supervisor. There was an oral delivery of information and authority to the person in charge and supervisor. There were officer vest and smoking areas were available in the campus canteen as equipment resources, although the area is still not eligible. From the disposition variable, there were commitments from the campus such as banning and overseeing cigarette sales and cigarette advertisements, installing no-smoking rules, cooperating with the security department to appeal to the academic community, and shifting the smoking area. There was also a joint discussion/evaluation related to the application. From the bureaucratic structure variable, there was no mechanism/SOP and a special organizational structure in the implementation of the non-smoking area. The conclusions is Non-smoking area policy implementation was not good enough. Suggestions that can be given and can improve the application of the non-smoking area need to develop policies/regulations on non-smoking zones and pay attention to policy steps/processes. AbstrakUniversitas X mengeluarkan SK Rektor yang memutuskan sebagai Kawasan tanpa rokok, namun di dalam Universitas X masih terdapat perokok yang melakukan aktivitas merokok. Penelitian ini bertujuan untuk mengetahui gambaran implementasi kebijakan Kawasan Tanpa Rokok di Universitas X Jakarta Barat tahun 2019. Penelitian ini menggunakan pendekatan kualitatif dengan melakukan wawancara mendalam, observasi, dan telaah dokumen. Informan dari penelitian ini berjumlah 9 orang. Hasil penelitian didapatkan dari variabel komunikasi sudah terdapat media yang digunakan untuk penyampaian pesan, sudah dilakukan peneguran dengan jelas walaupun tidak dilakukan secara konsisten.Â  Dari variabel sumber daya didapatkan sumber daya yang dilibatkan dan juga berperan merupakan seluruh civitas akademika, namun dalam proses penerapannya yang terlibat langsung yakni, Biro Umum dan Biro Kemahasiswaan sebagai penanggung jawab, Warek 3, ketua BEMU, dan Security sebagai pengawas. Selain itu, terdapat penyampaian informasi dan kewenangan kepada penanggung jawab dan pengawas secara lisan. Sedangkan terdapat rompi satuan petugas dan masih disediakannya Kawasan merokok di kantin kampus sebagai sumber daya peralatan. Namun, Kawasan merokok yang disediakan masih belum memenuhi syarat. Dari variabel disposisi sudah terdapat komitmen dari pihak kampus seperti melarang dan mengawasi penjualan rokok dan iklan rokok, memasang aturan dilarang merokok, bekerja sama dengan bagian security untuk menghimbau civitas akademika, dan melakukan penggeseran area merokok. Selain itu juga pernah dilakukannya pembahasan/evaluasi bersama terkait penerapan. Dari variabel struktur birokrasi belum terdapat mekanisme/SOP dan juga struktur organisasi khusus untuk implementasi kawasan tanpa rokok. Kesimpulan dari penelitian ini implementsi kebijakan kawasan tanpa rokok masih kurang baik. Saran yang dapat diberikan dan dapat memperbaiki penerapan Kawasan tanpa rokok yaitu perlu melakukan pengembangan tentang kebijakan/peraturan kawasan tanpa rokok dan memperhatikan langkah/proses kebijakan.